A study on the ocular findings and management of differently abled persons: North-East India - Hazarika, Himanto N.; Hazarika, Suranjana C. (International Journal Of Community Medicine And Public Health, 2018)
Background: The study of the objective was to evaluate the different ocular problems and proper management in differently abled persons (DAP). Methods: A randomised analysis of 530 DAP were done by a team of Ophthalmologists, Optometrists, Social workers and Psychologist, covering a few districts in North-East India, between August 2013 to July 2016 were included. Patients without parents’ consent were excluded. History was taken and IQ tested by Clinical Psychologist. Utmost care was taken during ocular examinations to obtain the best results. External ocular examination was done by slit lamp, ocular motility was tested, fundus examined by direct Ophthalmoscope, visual acuity tested by Cardiff cards and E-charts and refractive status determined by auto-refractometer. Results: Of the 530 persons examined, 304 (57.36%) male and 226 (42.64%) female; 144 (27.17%) were below and 386(72.83%) above 10 years. Mean IQ level was 44. A total number of 248 (46.8%) DAP had ocular problems. Most common being refractive error 115 (21.7%), squint 46 (8.68%), congenital ocular anomalies 34 (6.42%), cataract 28 (5.28%), Vitamin-A deficiency 15 (2.83%) and conjunctivitis 10 (1.89%).Among the 248 patients with ocular problems- 65 (26.21%) had down’s syndrome, 6 (2.42%) maternal infections and drug exposures, 42 (16.94%) postnatal infections, 9 (3.63%) head trauma. 115 cases were prescribed spectacles; 21 cataract cases undergone operation; Vitamin-A deficiency, conjunctivitis and other ocular problems were properly managed. Conclusions: Regular and periodic eye examination of these DAP and providing them with visual aid, proper treatment along with intensive training and counselling can help them to function in the society as a normal person.